Elusive Neck Carcinoma Simulating Idiopathic Intracranial Hypertension Due to Jugular Venous Outflow Obstruction - Case Report. (2nd November 2022) - Miller, Hayley V.; Wolin, Mitchell J.; Gardner, Stephen
ABSTRACT: Few cases have been reported of extra-cranial tumours in the neck causing intracranial hypertension due to jugular vein compression and consequent outflow obstruction. We present a case of a patient presenting with transient vision loss due to intracranial hypertension of unidentifiable cause on initial imaging workup. Upon further evaluation, the patient was found to have a neck tumour compressing the right jugular vein with stenosis of the ipsilateral transverse sinus – both contributing to his intracranial hypertension. Atypical patients presenting with symptoms concerning for intracranial hypertension may benefit from imaging below the level of the head to evaluate for extra-cranial causes.